Telmisartan Prevents Myocardial Fibrosis via Decreasing Fraction of Colagen Type 1 Volume in Myocardial Tissue in Wistar Rats-Induced High Salt Intake - Radiyati Umi Partan; Rachmat Hidayat; Mgs Irsan Saleh; Nita Parisa; Evi Lusiana; Nia Savitri Tamzil; Ayeshah Augusta Rosdah; Muhammad Reagen (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2017)
Myocardial fibrosis is a pathological condition that responsible for initiation of heart failure. Neurohormonal endogen, angiotensin II, has a potential role to activate endothelin I, TGF-Î²1, myocardial fibroblast, extracelullar matrix deposition, structural changes and decreasing of cardiac function. Fibrotic process is also influenced by PPAR Î³. Telmisartan has a potential effect to inactivate angiotensinergic system and to activate PPAR Î³. It is expected that telmisartan has optimal effect to protect myocardial fibrosis. To know the role of variation dose of telmisartan to decrease collagen type 1 fraction volume in cardiac tissue of Wistar rats. Ten-week-old male Wistar Rat (n = 30) were randomized into five groups, and each group consisted of 6 rats. Group 1 : negative control. Group 2 : rats were induced by intake Nacl 8% doses 2% body weight for eight weeks. Group 3 : rats were induced by intake Nacl 8% doses 2% body weight and telmisartan 3 mg/kgBB for eight weeks. Group 4 : rats were induced by intake Nacl 8% doses 2% body weight and telmisartan 6 mg/kgBB for eight weeks. Group 5 : rats were induced by intake Nacl 8% doses 2% body weight and telmisartan 12 mg/kgBB for eight weeks. Collagen volume fraction was assessed by immunohistochemistry and ImageJ program. ANOVA test followed pos hoc test was used to analyzed each variable. Collagen volume fraction significantly decreased in group 3, 4 and 5 compared in group 2. Telmisartan decreases collagen type 1 volume fraction of myocardial tissue .